Researching Determinantsaffecting Foreign Trade Business Risk: A Case Of Small And Medium Enterprises In Dong Nai Province - Bich, Van Thi (Journal of Business Management and Economics, 2017)
Nowadays, foreign trade plays very important role in the economic development of any country. Especially, Vietnam also exports a lot of agricultural products to other countries and imports the capital goods from other countries. Therefore, it is not wrong to say that economic development of a country depends of foreign trade. Besides, foreign trade provides foreign exchange that can be used to remove the poverty and other productive purposes.The demand factor plays very important role in increasing the production of any country. The foreign trade expands the market and encourages the producers. In Vietnam,domestic market is very limited due to low income and others. So it is necessary to solve the problem we should sell our product in other countries.This is reason;the researcher had done thisstudy.There were 200managers of small and medium enterpriseswho interviewed and answered about 21 questions. The Data collected from April2016 to April 2017. This study had been analyzed Cronbach’s Alpha, KMO testing and the result of KMO testing used for the next research of the regression. Managersâ€™ responses measured through an adapted questionnaire on a 5-point Likert scale (Conventions: 1: Completely disagree, 2: Disagree, 3: Normal; 4: Agree; 5: completely agree). Hard copy and online questionnaire distributed among 12.000 managers of small and medium enterprises. In addition,five components affecting the foreign trade business riskof small and medium enterprises (SMEs) in Dong Nai provincewith significance level 5 percent and then the researcher haspolicies improving the foreign trade business risk in the future.